Association between cartilage and bone biomarkers and incidence of radiographic knee osteoarthritis (RKOA) in UK females: a prospective study. - Blumenfeld, O; Williams, F; Hart, D; Spector, T; Arden, N; Livshits, G (2013)
OBJECTIVE: There is a need to find biochemical markers that would identify people with increased risk of developing radiographic knee osteoarthritis (RKOA). The aim of this study was to evaluate the ability of cartilage and bone biomarkers (cartilage oligomeric matrix protein (COMP), aggrecan, cellular inhibitor of apoptosis protein (cIAP), N-telopeptide-to-helix (NTx)) to predict RKOA incidence in a 10-year follow-up of UK females from the Chingford community study. METHOD: Joint space narrowing (JSN), osteophytes (OSP) and Kellgren-Lawrence (K/L) grades were scored from radiographs of both knees at study baseline and 10 years later in 1,003 women aged 45-64. Circulating levels of biomarkers and demographic variables were measured at baseline. Statistical association analysis was conducted between the potential predictor factors measured at baseline and documentation of RKOA at 10-year follow-up. RESULTS: Age and body mass index (BMI), were significant predictors of incidence of RKOA as assessed by K/L and OSP. Considering biomarkers, independent significant association was found between COMP circulating levels and K/L scores (Odd Ratio (OR) = 2.87, 95% Confidence Interval (CI) = 1.19-6.89, P = 0.018). Significant negative association was detected between aggrecan plasma concentrations and JSN, with OR = 0.37 (95% CI 0.15-0.89), P = 0.026. CONCLUSIONS: Aggrecan and COMP circulating levels contribute to identification of phenotype-specific RKOA incidence. These data suggest potentially protective role of aggrecan in cartilage loss, as measured by JSN. High COMP levels are risk factors for development of RKOA, as assessed by K/L scores.